Embodied Carbon Premium for Cantilevers - Helal, James; Trabucco, Dario; Ruggiero, David; Miglietta, Paola; Perrucci, Giovanni (Buildings (Basel), 2024)
This study addresses the critical need for sustainable architectural designs within the context of climate change and the significant role the built environment plays in greenhouse gas emissions. The focus of this paper is on understanding the influence of unbalanced cantilevers on the embodied carbon of structural systems in buildings, a subject that has, until now, remained underexplored despite its importance in architectural innovation and environmental sustainability. Employing a case study approach, the Melbourne School of Design (MSD) building serves as a primary example to assess the embodied carbon implications of cantilevered versus supported structures. The methodological framework encompasses a comparative embodied carbon assessment utilising an input–output-based hybrid life cycle inventory analysis approach. The findings reveal that unbalanced cantilevers in buildings, exemplified by the MSD building, can lead to a 10% increase in embodied carbon compared to alternative designs incorporating supporting columns. Such findings underscore the environmental premium for cantilevers, prompting a re-evaluation of design practices towards minimising embodied carbon. Through this investigation, the research contributes to the broader discourse on sustainable construction practices, offering valuable insights for both design practitioners and educators in the pursuit of improving the environmental performance of the built environment.